2004
DOI: 10.1021/ac035209k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectrospray Ionization of Protein Mixtures:  Solution pH and Protein pI

Abstract: Solutions consisting of single proteins and mixtures of proteins at different pH values have been subjected to both positive ion and negative ion nanoelectrospray ionization to study the influence of solvent pH and protein pI on the ionization responses of proteins. As has been noted previously, it is possible to form protein ions of one polarity despite the fact that the proteins are present as the opposite polarity in solution. However, total response under this condition tends to be at least an order of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 63 publications
6
64
1
Order By: Relevance
“…The greater response for the ␣-chain is presumably due to its greater basicity (␣-chain pI ϭ 8.7, ␤-chain pI ϭ 6.8) because both chains coeluted in the chromatographic clean-up step. While both proteins are expected to be positively charged under these solution conditions, it has been observed that the greatest positive ion electrospray responses are observed when the solution pH is roughly 5 units lower than the protein pI [49]. For this study, this discrimination in ionization yield is advantageous in that most of the excess charge of the nanospray droplets is partitioned into the ␣-chain ions.…”
Section: Resultsmentioning
confidence: 96%
“…The greater response for the ␣-chain is presumably due to its greater basicity (␣-chain pI ϭ 8.7, ␤-chain pI ϭ 6.8) because both chains coeluted in the chromatographic clean-up step. While both proteins are expected to be positively charged under these solution conditions, it has been observed that the greatest positive ion electrospray responses are observed when the solution pH is roughly 5 units lower than the protein pI [49]. For this study, this discrimination in ionization yield is advantageous in that most of the excess charge of the nanospray droplets is partitioned into the ␣-chain ions.…”
Section: Resultsmentioning
confidence: 96%
“…McLuckey and coworkers [21] measured the signal intensities (related directly to the ionization efficiency) of analyte ions from protein mixtures electrosprayed at various pH values and deterAddress reprint requests to C.…”
mentioning
confidence: 99%
“…McLuckey and coworkers [21] measured the signal intensities (related directly to the ionization efficiency) of analyte ions from protein mixtures electrosprayed at various pH values and deter-mined that the main parameter influencing ionization efficiency was the protein surface charge. Likewise, Kuprowski and Konermann [22] showed that the signal intensity of ions from ESI of denatured proteins with higher surface charge is greater than the signal intensity of ions from the ESI native state proteins.…”
mentioning
confidence: 99%
“…Their net charge in solution is negative, resulting in significantly lower ion yields using ESI of the opposite polarity [63]. However, ECD of doubly-protonated nucleic acids [64] or CAD of multiply-charged protein anions [7] can provide useful structural information.…”
Section: Methods For Dissociation Of Multiply-charged Biomolecular Ionsmentioning
confidence: 99%